A near-infrared ratiometric fluorescent probe based on the CN double bond for monitoring SO2 and its application in biological imaging. Issue 5 (27th January 2020) - Zhang, Tiange; Zhu, Linlin; Ma, Yanyan; Lin, Weiying
Abstract : A near-infrared ratiometric fluorescent probe based on CN double bond was developed for monitoring SO2 and its application in biological imaging. Abstract : Sulfur dioxide (SO2 ) is commonly used in food processing and preservation processes due to its antioxidant and antibiotic properties. However, it has been documented that excessive intake of SO2 could cause serious health problems. Therefore, it is very necessary to develop a novel SO2 probe with excellent performance. Herein, a novel fluorescent probe (Ph-CN ) based on the ICT–ESIPT mechanism for monitoring SO2 with the CN double bond was developed. Furthermore, Ph-CN exhibits various splendid features, such as near-infrared (NIR) and ratiometric detection, real-time detection (<5 s), good selectivity and photostability, large Stokes shift (230 nm) and large emission shift (200 nm). Most importantly, the probe Ph-CN can realize the detection of SO2 in HeLa cells and in vivo .